Oral tradition, epistemic dependence, and knowledge in African cultures - Ikuenobe, Polycarp (Array, 2019)
This paper examines the nature and legitimacy of oral tradition as a method of acquiring, archiving, retrieving, and transmitting knowledge, beliefs, values, and practices in traditional African communal cultures. I argue that oral tradition, which involves parables, proverbs, myths, art, and folklore, also involves relying on elders as the repositories of knowledge and tradition. I argue that this reliance can be justified based on the principles of epistemic trust, epistemic dependence, and epistemic communalism. The notion of epistemic communalism, which involves epistemic division of labour and epistemic comparative advantage, requires a multidisciplinary holistic approach to knowledge in Africa. This communal method of acquiring knowledge indicates how people accept beliefs and justify their acceptance of beliefs as members of an organically integrated community. This underscores the need for mutual dependence among philosophy and other disciplines such as history, anthropology, literature, and science as the source and basis for African knowledge.